Theories and Concept of Interstellar Movie (2014) by Christoper Nolan - Adelia, Salsa Maya (LPPM Universitas Mercu Buana Yogyakarta, 2023)
The purpose of this study was to briefly describe the theories and concepts found in Interstellar films. The film's concepts and theories became interesting for those who watched it, as many such concepts and theories were difficult to solve. The method used in this study is a qualitative descriptive study, which is the researcher analyzing the reality or events in this film. The data that will be collected will be done by watching the movie more carefully and then recording what is related to the theories and concepts that are in the discussion and then searching for a journal or video related to what is discussed. The results of this study suggest that there are several theories about the film. These are The Gravity Anomaly, The Wormhole, The Theory of Relativity of Time and Space, The Gargantua, and The Tesseract Theory. Interstellar is an interesting film to watch because the theories and concepts contained learning that could be learned.Â Â